Dari Antroposentrisme Menuju Ekosentrisme: Diskursus Pengelolaan Lingkungan dan Tata Ruang Bali - Wahyudi Arimbawa; I Kadek Ardi Putra (Jurnal Ecocentrism, 2021)
This article presents a critical discourse on environmental management and spatial planning in Bali. Using Foucault's (1973) theory, this article presents an empirical discourse on environmental degradation in Bali as a breakthrough in thinking awareness. Through an in-depth literature review, this article begins with (1) describing the construction of ideas on environmental management and spatial planning, and (2) presenting Balinese philosophical values and views in building awareness of ecocentrism. This study is expected to provide a systemic perspective on how the value system that is believed to be the socio-cultural view of the Balinese people is translated into spatial planning and its environment. This discourse then leads to the context that in the sociocultural view of the Balinese people, everything that exists in nature is interdependent as a unified ecosystem that must be maintained and preserved. At the ecocentrism level, the Balinese people's philosophy of life believes in the values of deep respect for all aspects of life, starting from the biotic-abiotic components, animals, plants and everything on earth as a manifestation of the concept of tat twam asi.